Effectiveness of a group-based program for parents of children with dyslexia - Multhauf, Bettina; Buschmann, Anke; Soellner, Renate (Reading and writing, 2016)
Parents of children with dyslexia experience more parenting stress and depressive symptoms than other parents. The purpose of this study was to evaluate the effects of a cognitive-behavioral group-based program for parents of dyslexic children on parenting stress levels, parent-child homework interactions and parental competencies. 39 children with dyslexia and their mothers were randomly assigned either to a cognitive-behavioral-therapy group or a waiting-list control group. The intervention lasted for 3 months. Mothers filled in the Parenting Stress Index and a paper-pencil questionnaire assessing dyslexia specific stress, conflicts in homework situations and competencies in dealing with dyslexia. Assessment took place before, immediately after, and 3 months following intervention. A multivariate analysis of variance revealed overall effectiveness of the program (partial η2 = .091), which can be mainly attributed to the reduction of parenting stress and dyslexia specific stress as well as an enhancement of parental competencies. Planned contrasts showed that effects could not be approved directly after the training but 3 months later, indicating a delayed effect. Future studies should examine program effects on mothers and fathers on the basis of a larger representative sample.